"I just have to move on": Women's coping experiences and reflections following their first year after primary breast cancer surgery. (April 2016) - Drageset, Sigrunn; Lindstrøm, Torill Christine; Underlid, Kjell
Abstract: Purpose: The purpose of this qualitative follow-up study was to describe women's individual coping experiences and reflections following their first year after primary breast cancer surgery. Methods: Using a qualitative descriptive design, we collected data through individual interviews with ten women at a Norwegian university hospital between August 2007 and April 2008. We employed Kvale's method of qualitative meaning condensation analysis. Results: Themes identified were: existential concerns and finding meaning, ways of thinking and feeling about the disease, taking action, and returning to normal life. Most women experienced an increased appreciation of life and greater confidence in themselves, were more caring and compassionate towards others, and focused more on their life priorities. Their family and close relationships became more important. They accepted their situation and made the best of it. Positive thinking, physical activity, self-care, nature, hobbies and work helped. Generally, they were optimistic despite a fear of cancer recurrence and uncertainty about their future. The women wanted to return to a "normal" and healthy life by distancing themselves from both the cancer environment and information about cancer. Conclusion: Uncertainty and anxiety about a potential future cancer relapse was a major undercurrent one year following surgery. Our findings emphasize the richness in these women's coping strategies, their different coping profiles and different needs, as well as some general adaptive strategies, which all fluctuated over time. Not all managed to cope equally well. Through awareness of these women's individual experiences and coping strategies, healthcare professionals can enhance these women's coping endeavours. Highlights: This study highlights women's coping experiences after breast cancer surgery. Uncertainty and anxiety about a potential future relapse was a major undercurrent. Adaptive coping was finding meaning, taking action, physical activity, normalization. Negative factors were existential concerns and the fear of recurrence.